“I CAN’T RESIST TIKTOK”: EXPLORING THE INFLUENCE OF CELEBRITY ENDORSEMENT, PARASOCIAL INTERACTION, AND FOMO ON GEN-Z PURCHASE INTENTION - Oktavian, Rizal Boy; Dermawan, Rizky; Majid, Nurkholish (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research aimed to examine the influence of celebrity trustworthiness, celebrity attractiveness, parasocial interaction, and fear of missing out (FOMO) on purchase intention among TikTok users in the management student community. The population consisted of active undergraduate management students at the Universitas Pembangunan Nasional "Veteran" Jawa Timur who use TikTok. The sampling technique employed was purposive sampling based on specific criteria. The study utilized a quantitative approach, and data was collected through a survey questionnaire. The key findings revealed that celebrity attractiveness and FOMO had a significant positive influence on purchase intention, while celebrity trustworthiness and parasocial interaction did not contribute to purchase intention. In conclusion, marketers should focus on leveraging celebrity attractiveness and creating a FOMO effect to effectively target the Generation Z consumer segment on the TikTok platform. Keywords: Celebrity Endorsement; Parasocial Interaction; FOMO; Purchase Intention; Generation Z